Dihydro-β-agarofuran-type sesquiterpenes from the roots of Tripterygium wilfordii and their cytotoxic activity. (April 2020) - Jiang, Yi-Yu; Li, Ban-Ban; Li, Na; Meng, Xiao; Lin, Xin; Wang, Dong; Xiong, Da-Xi; Sun, Ya-Nan; Chen, Li; Cui, Long
Graphical abstract: Highlights: Eight new compounds (2, 6, 8 -13 ) were isolated from the roots of T. wilfordii . Compounds 6, 7, 10, 11 displayed a high selectivity for inhibitory cancer cells. This article and studying of dihydro- β- agarofuran-type sesquiterpenes nature products have bright future in the preventment and treatment of numerous cancer. Abstract: Twenty-one β- dihydroagarofuran-type sesquiterpenes compounds were isolated from the dry roots of Tripterygium wilfordii, including eight new β- dihydroagarofuran-type sesquiterpenes nature products (2, 6, 8 -13 ) and thirteen known compounds, the structure of these compounds were elucidated by extensive NMR spectroscopic and mass spectrometric analysis. Among all isolated compound 10 exhibited cytotoxicity toward five carcinoma cells, including A549, HOS, MCF-7, MDA-MB-231 and MCF7/TAMR cells, with half-maximal inhibition of cell proliferation values ranging from 13.77 to 25.19 μM.